Reviewing EKGs in Thalassemia Patients to Evaluate Their Cardiac Function - Abdolhamid Bagheri; Mitra Karimi; Hojat Afradi; Mahmoud Hadipour Dehshal (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Introduction: There are more than 18000 thalassemia patients in Iran. In a current study, a high rate of mortality in these patients due to heart failure, is shown. Main factors for evaluating this disorder in thalassemia patients were their electrocardiograms (EKGs) and Serum Ferritin Levels (SFLs).Methods: We studied the cardiac function in 91 patients (73 major and 18 intermediate thalassemia patients) treated in Zafar Thalassemia Center, of whom 35 (38.45%) were male and 56 (61.55%) were female. The Factors in this study contains: EKGs, mean annual serum ferritin (at least, three SFL had been recorded in each patient treatment file in 2009), mean annual hemoglobin (Hb) levels and mean annual hematocrit (Hct) levels (average, 12 recorded hematocrit levels during 2009).Results: Our findings have shown that Q-T interval did not correlate with ferritin (r = 0.05, P > 0.05). In both patients with LVH and without LVH, there was no significant difference in SFL (P > 0.05). Although, the mean rate among the thalassemia patients was 85.34 ± 12.91, it did not correlate significantly with QRS duration and P-R Interval (r = -0.08, P > 0.05). In addition, ferritin did not correlate significantly with QRS duration and P-R Interval (r = 0.1, r = 0.05 and P > 0.05, P > 0.05). Furthermore, there was no difference in SFL in patients with normal cardiac axis and those with cardiac axis deviation.Conclusion: There is no correlation between SFL and variations in EKG. Although EKG is an available method for checking cardiac function in thalassemic patients, especially in developing countries, physicians cannot rely on it for diagnosis or prognosis of cardiac failure in thalassemia patients. Therefore, other methods such as MRIT2* and Echocardiography are suggested to be used periodically in order to check the cardiac function in thalassemia patients.